Efficient power aware and reputation-based routing protocol for MANET - Gomathi, S.S.; Chbeir, R.; Krishnamurthi, S. (Journal of Digital Information Management, 2008)
Energy conservation is a critical issue in Mobile Ad hoc Networks (MANETs) for node and network life, as the nodes are powered by batteries only. In order to maximize the lifetime of MANETs, traffic should be sent through a shortest path that does not contain nodes with low residual energy and consumes minimum total transmission power. The above objectives cannot be satisfied simultaneously by applying the existing power aware routing algorithms. For this reason, several power-aware routing approaches have been proposed in the literature attempting to maximize the network lifetime. An interesting approach called Minimum Drain Rate (MDR) aims to predict the lifetime of nodes according to the current traffic conditions. However, it does not guarantee that the total transmission power is minimized over a chosen route. In this paper, we provide an new approach called Secure Extended Optimal Energy Drain Rate (SEOEDR) able to extend the MANET lifetime and duration of the path, and also to minimize the total transmission power consumed per packet. In our approach, the traffic is routed such that the energy consumption is balanced among the nodes in proportion to their energy reserves. We also handle the selfishness of nodes by considering the node reputation while making the routing decisions. It results in selection of routes that are simultaneously energy efficient and reliable. The simulation results that we have conducted during our study show the relevance of our algorithm, in terms of energy saving and overall network lifetime, in comparison with existing ones.
Cited By (since 1996):6Export Date: 10 July 2014
Keywords: Battery cost; DSR; Energy efficient routing protocol; MAC layer; MANET; NIC

Impact of node mobility on MANET routing protocols models - Divecha, B.; Abraham, A.; Grosan, C.; Sanyal, S. (Journal of Digital Information Management, 2007)
A Mobile Ad-Hoc Network (MANET) is a self-configuring network of mobile nodes connected by wireless links to form an arbitrary topology without the use of existing infrastructure. In this paper, we have studied the effects of various mobility models on the performance of two routing protocols Dynamic Source Routing (DSR-Reactive Protocol) and Destination-Sequenced Distance-Vector (DSDV-Proactive Protocol). For experiment purposes, we have considered four mobility scenarios: Random Waypoint, Group Mobility, Freeway and Manhattan models. These four Mobility Models are selected to represent possibility of practical application in future. Performance comparison has also been conducted across varying node densities and number of hops. Experiment results illustrate that performance of the routing protocol varies across different mobility models, node densities and length of data paths.
Cited By (since 1996):36Export Date: 10 July 2014
Keywords: MANET; Mobile adhoc networks; Mobility models